Aktivitas Kelompok: Menggambar terhadap Halusinasi Dengar pada Pasien Skizofrenia - Putri, Nindya Erina; Oktaviana, Wita; Wibowo, Slamet (Jurnal Keperawatan Profesional (KEPO), 2024)
Mental disorders occur due to disturbances in the thought process, emotions, and behavior, which cause maladaptive responses. Schizophrenia is one of the most common mental disorders, characterized by impaired cognitive function. One of the symptoms that often appears in schizophrenia is sensory perception disorders, especially auditory hallucinations. The purpose of this study was to determine the difference in the scale of auditory hallucinations before and after being given Group Activity Therapy (TAK) drawing intervention. The results of observations in the Nakula Room of Dr. Arif Zainudin Mental Hospital showed that the majority of patients experienced auditory hallucinations. This study used a quasi-experimental design with a one-group pretest-posttest approach. The sampling technique used was total non-probability sampling, involving 6 patients who experienced sensory perception disorders: auditory hallucinations. The instrument used in this study was the Auditory Hallucination Rating Scale (AHRS) questionnaire. Data analysis was carried out using the Wilcoxon Signed-Rank test, which showed a significance value of 0,027 (p-value <0,05). This indicates a significant difference in the scale of auditory hallucinations before and after being given group activity therapy drawing. Group drawing activity therapy has a significant effect on the ability to control auditory hallucinations in schizophrenia patients.